Hubungan Gerakan Berulang terhadap Gejala Nyeri Tangan pada Pekerja Bagian Tenun di Industri Lurik Indah Klasik Klaten - Muh Dicky Tegar Santoso; Farhana Syahrotun Nisa Suratna; Reni Wijayanti (Journal of Applied Agriculture, Health, and Technology, 2025)
Weaving workers at the Lurik Indah Klasik Industry in Klaten are at risk of experiencing healthproblems caused by repetitive movements performed over long periods. One of the most commoncomplaints is hand pain, which can result from continuous muscle and joint strain without sufficientmovement variation or adequate rest. The weaving activity requires constant use of the hands and wrists,which increases the risk of muscle fatigue and musculoskeletal disorders. This study aims to determinethe relationship between repetitive movements and hand pain symptoms among weaving workers atLurik Indah Klasik Industry, Klaten. The research design employed an observational analytic approachwith a cross-sectional method. The study population consisted of 28 workers, and all were included asresearch subjects using the total sampling technique. The instrument used to assess pain levels was theNumeric Rating Scale (NRS), while the relationship analysis was conducted using the Somers’d test.The results showed a significant relationship between repetitive movements and hand pain symptoms,with a correlation coefficient (r) of 0.583, indicating a moderate relationship. These findings suggestthat the higher the frequency and duration of repetitive movements, the more likely workers are toexperience hand pain. Therefore, ergonomic interventions such as implementing rest breaks,introducing movement variation, and improving working posture are recommended to reduce the riskof hand pain among weaving workers.